Design for quality assurance - Aarthi Dhinakaran (2013)
Companies and businesses needs customer feedback to help business uncover flaws so that they can act on it. One of the main goals of gathering customer feedback is to enable communications between the business and its customers. However it may be tedious to use paper survey alone without